Plasma free captopril concentrations during short and long term treatment with oral captopril for heart failure. Issue 2 (August 1985) - Shaw, T R; Duncan, F M; Williams, B C; Crichton, E; Thomson, S A; Davis, J R; Rademaker, M; Edwards, C R
Abstract : Plasma free captopril concentrations and haemodynamic response to captopril were studied in 20 patients with severe chronic heart failure. A 25 mg oral dose of captopril produced a 36% reduction in systemic vascular resistance, with individual responses varying from 13% to 64%. Mean systemic pressure fell by 20% and cardiac output rose 28%. The absorption of captopril was rapid. Peak plasma free captopril concentration occurred at 45 minutes after the dose and was followed by a smaller second peak. Peak plasma free captopril concentrations varied more than 20-fold but did not correlate with the maximal reduction in systemic vascular resistance. Elimination half life was seven hours. Fourteen patients were restudied after 1-2 months of captopril treatment and 12 showed symptomatic benefit. There was a sustained improvement in haemodynamic state and in non-invasive indices of myocardial function. During long term treatment the predose plasma free captopril concentration correlated well with dosage, but steady state captopril concentrations did not show a significant relation with haemodynamic response. On a dosage regimen of 25-50 mg three times daily the morning predose plasma free captopril concentration and plasma renin activity were relatively low and suggested that maximal inhibition of the renin-angiotensin system was not maintained throughout the dosage interval.